Isolated Nocturnal Hypertension in Children - Awazu, Midori (Frontiers in Pediatrics, 2022)
Isolated nocturnal hypertension (INH) is attracting attention because it has been reported to correlate with target organ damage and cardiovascular events in adults. INH has also been reported in children especially in those with underlying diseases including chronic kidney disease and is associated with markers of early target organ damage. INH consists the major part of nocturnal hypertension. On the other hand, masked hypertension is largely attributed to INH. INH is usually diagnosed by ambulatory blood pressure monitoring. Recently it has become possible to measure sleep blood pressure by automated home blood pressure device feasible also in children. The epidemiology, methodology and reproducibility, pathophysiology, relation to target organ damage, and treatment of INH in children will be reviewed here along with adult data.